INDUCING SOME SECONDARY METABOLITES FROM CALLUS CULTURES DERIVED FROM Plantago psyllium AND Plantago major EXPOSED TO COBALT STRESS - Neamah, S. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This experiment was conducted to study the influence of cobalt concentrations on the production of seven flavonoid compounds in callus derived from Plantago psyllium L. and Plantago major L. Results showed that the best combination of 2,4-D and kinetin concentrations add to Muroshige and Skoog medium to obtain the highest fresh weight of 541.0 mg was 3.0 and 1.0 mg.L-1 respectively. psyllium stimulated callus produced the highest fresh weight of 365.7 mg. The addition of 75 ppm of cobalt resulted in a significantly lower fresh weight of P. psyllium callus (139.8 mg). The interaction between Plantago species and cobalt concentrations was significant. The callus inducted from P. major had significant increases of the scutallarein, apigenin, nepetin and luteolin compounds with 26.40, 22.64, 14.93 and 26.20 µg.100mg-1 dry weight, respectively. The production of the hispidulin compound was increased in P. psyllium at 29.40 µg.100mg-1 dry weight. Also, the addition of cobalt metal stimulated the production of flavonoids at 50 ppm cobalt producing the highest amounts of hispidulin and luteolin at 40.30 and 41.60 µg.100mg-1 dry weight, respectively. Meanwhile, 75 ppm cobalt treatment produced the highest amount of scutallarein, apigenin, nepetin and aucubin at 25.61, 23.25, 15.90 and 13.70 µg.100mg-1 dry weight, respectively. The callus inducted from P. major treated with 50 ppm of cobalt showed the highest production of scutallarein, apigenin and luteolin at 30.33, 32.26 and 51.90 µg.100mg-1 dry weight respectively. Baicalein reached 16.46 µg.100mg-1 dry weight, at 75 ppm of cobalt metal treatment in callus inducted from P. psyllium.